Ambulatory blood pressure and arterial stiffness web‐based telemonitoring in patients at cardiovascular risk. First results of the VASOTENS (Vascular health ASsessment Of The hypertENSive patients) Registry. Issue 8 (11th July 2019) - Omboni, Stefano; Posokhov, Igor; Parati, Gianfranco; Rogoza, Anatoly; Kotovskaya, Yulia; Arystan, Ayana; Avolio, Alberto; Barkan, Vitaliy; Bulanova, Natalia; Cardona Muñoz, Ernesto; Grigoricheva, Elena; Konradi, Alexandra; et al.
Abstract: The VASOTENS Registry is an international telehealth‐based repository of 24‐hour ambulatory blood pressure monitorings (ABPM) obtained through an oscillometric upper‐arm BP monitor allowing combined estimation of some vascular biomarkers. The present paper reports the results obtained in 1200 participants according to different categories of CV risk. Individual readings were averaged for each recording and 24‐hour mean of brachial and aortic systolic (SBP) and diastolic blood pressure (DBP), pulse wave velocity (PWV), and augmentation index (AIx) obtained. Peripheral and central BP, PWV and AIx values were increased in older participants (SBP only) and in case of hypertension (SBP and DBP). BP was lower and PWV and AIx higher in females. PWV was increased and BP unchanged in case of metabolic syndrome. Our results suggest that ambulatory pulse wave analysis in a daily life setting may help evaluate vascular health of individuals at risk for CV disease.